Optimization of enzymatic sugar beet hydrolysis in a horizontal rotating tubular bioreactor. Issue 3 (19th July 2016) - Andlar, Martina; Rezić, Iva; Oros, Damir; Kracher, Daniel; Ludwig, Roland; Rezić, Tonči; Šantek, Božidar
Abstract: BACKGROUND: Sugar beet pulp (SBP) is a promising feedstock for the production of 2nd generation biofuels, but efficient enzymatic hydrolysis remains a key challenge; therefore, new process designs and/or bioreactor designs are crucial to overcome this hurdle. In this regard, horizontal rotating tubular bioreactors (HRTB) offer the advantage of high substrate loadings while minimizing the space and energy demand compared with conventional stirred tank reactors. Here, a statistical approach is used to optimize the hydrolysis of sugar beet pulp in laboratory experiments, and it is shown that such a process can be implemented in a HRTB. RESULTS: Using the design of experiments (DOE) method, the reaction conditions of four commercial enzyme mixtures (Ultrazym AFP‐L, Viscozyme L, Pectinase and Cellulase) was optimized for the degradation of SBP in small‐scale experiments. Using Ultrazym AFP‐L as the most efficient mixture, a 10 L scale conversion was performed in a HRTB. At a substrate loading of 135 g L −1 and optimized conversion parameters (enzyme load, pH and rotating speed of the reactor), 0.525 W dm −3 were needed to achieve solubilisation of 30% of the total mass of initial SBP after 24 h. CONCLUSION: DOE was found to be an easy‐to‐apply method that allowed optimizing the conditions for enzymatic hydrolysis of SBP, resulting in a higher sugar yield. The results could be transferred to an HRTB, which is a suitable system for enzymatic conversion and efficient saccharification of semi‐solid or solid substrates with relatively low energy consumption. © 2016 Society of Chemical Industry